Validation of OpenMC Code for Low-cycle and Low-particle Simulations in the Neutronic Calculation - Mabruri, Ahmad Muzaki; Syarifah, Ratna Dewi; Aji, Indarta Kuncoro; Arkundato, Artoto; Trianti, Nuri (Jurnal Ilmu Fisika, 2024)
Validation of Low-Cycle and Low-Particle OpenMC Simulation Codes for Neutronics Calculations has been conducted. This study validates OpenMC, an evolving open-source neutron analysis code. Validation of Low-Cycle and Low-Particle Codes is crucial as it allows for effective calculations with minimal computational resources. Determining the convergence point of cycles and minimum particles in low-cycle and low-particle calculations enables maintaining calculation accuracy, thus providing sufficiently accurate results. This study demonstrates that a minimum of 15,000 particles, 100 cycles (30 inactive, 70 active), is required for low-cycle simulations. A comparison of k-eff calculation results with the SRAC code for MSR FUJI-12 at 7 burnup points (0-27 MWd/ton) yields a maximum error of 0.7%. These results validate the effectiveness of OpenMC in achieving accurate neutronic calculations with limited computational resources